The Promise and Perils of Infrastructure Privatization - Solomon, L. author. aut Link
VI, 202 p.
Keywords: This book focuses on the Macquarie Group Ltd. From its modest beginnings in Australia, Macquarie has achieved preeminence as the world's leading non-governmental operator of infrastructure assets. Its infrastructure fund model leases (or buys) staid assets ranging from toll roads to airports, piles on debt and reaps handsome rewards.